Left atrial appendage cannulation for left ventricular unloading in a patient with ventricular thrombus on extracorporeal life support - Anne-Kristin Schaefer; Dominik Wiedemann; Gottfried Heinz; Julia Riebandt; Robert Zilberszac (Journal of Cardiothoracic Surgery)
Abstract Background Left ventricular unloading is needed in patients on extracorporeal life support (ECLS) with severely impaired left ventricular contractility to avoid stasis and pulmonary congestion, and to promote LV recovery. The presence of thrombi in the LV precludes the use of conventional active unloading methods such as transaortic microaxial pumps or apical LV vents. We describe placement of a vent cannula via the left atrial appendage (LAA) as a useful bailout option. Case presentation A 61-year-old patient presenting with normotensive cardiogenic shock (SCAI C) after subacute anterior wall myocardial infarction deteriorated with pulmonary edema and ventricular fibrillation, requiring veno-arterial extracorporeal life support under ongoing CPR (SCAI E). An Impella CP was placed for LV unloading, but was unable to generate flow and was thus removed. A large left ventricular thrombus was detected as the cause for insufficient Impella flow. For urgent LV unloading, we placed a vent cannula via the LAA through a thoracotomy to bridge our patient to total artificial heart implantation. However, intraoperative TEE showed resolution of the LV thrombus, enabling to change the strategy to left ventricular assist device implantation only, which was performed successfully. Our patient made a full recovery and is now doing well in regular outpatient follow ups. Conclusions ECLS provides excellent circulatory support at the price of a high complication burden and considerable LV afterload increase. ECLS complications often require individualized solutions not represented in current heart failure guidelines. This patient has developed a dreaded and nearly always fatal ECLS complication, which was successfully managed with vent placement via the LAA. Graphical Abstract